A98 VASOACTIVE INTESTINAL PEPTIDE PROMOTES TH17 IMMUNE RESPONSES THEREBY PROTECTING AGAINST CITROBACTER RODENTIUM INDUCED COLITIS. (1st March 2018) - YU, H; Wu, X; Yang, H; Celiberto, L S; Graef, F A; Bosman, E S; Ma, C; Huang, T; Reid, G; Vallance, B; Jacobson, K
Abstract: Background: Vasoactive intestinal peptide (VIP), a 28 amino acid neuropeptide, exhibits potent anti-inflammatory effects in autoimmune and inflammatory diseases. Interestingly, recent ex vivo studies suggest that VIP can promote the production of proinflammatory Th17 cells (primarily secrete cytokine IL-17A). While Th17 cells likely aggravate inflammation in autoimmune diseases, they are known to be protective against Citrobacter rodentium induced colitis-a mouse model of colitis. Aims: The aim of this study was to examine the in vivo significance of VIP-Th17 signaling axis during an enteric pathogen ( Citrobacter rodentium ) infection. Methods: Wild type mice, VIP deficient ( Vip -/ - ) mice and VIP treated Vip -/ - mice were infected with C. rodentium for 10 days. Body weight loss and survival rates were recorded daily. Bacterial counts in the intestinal and systemic sites were determined by an in vivo imaging system and plating method. Mucosal damages were analyzed by Haemotoxylin and Eosin staining. The production of cytokines (such as IL-1β, IL-6, IL-17A, IL-22 and TNF-α) were quantified by quantitative PCR, ELISA and FACS. Results: Vip -/ - mice infected with C. rodentium showed dramatic body weight loss, decreased survival rates, increased bacterial colonization in intestinal and systemic sites, worsened mucosal damages/inflammatory responses as well as reduced production of Th17 cell responses. Importantly, exogenous treatment of Vip -/ - mice with recombinant VIP ameliorated C. rodentium -induced colitis, accompanied by restoration of Th17 cell responses. Conclusions: We provide the first in vivo evidence that VIP promotes Th17 immune responses thereby protecting against C. rodentium induced colitis. Funding Agencies: CCC